Technical worker’s participation in the CVET and company competitiveness - Figueira, Eduardo; Rosa, Vítor; Koehnen, Timothy; Cordeiro, Ana; Fragoso, António; Amaro, Rogério Roque; Ribeiro, Filipe; Tomé, Lídia (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The present study intends to understand how factors influence employed adults’ decision to participate in learning activities in two sectors of the five regions (NUT II) of the Portuguese continental territory. The factors associated to individuals’ participation in Continuing Vocational Education and Training (CVET) constitute an important issue to be studied given the need to understand why adults participate in CVET activities. This is important because continuing professional qualification of workers is assumed to be essential to improve workers’ employability and productivity in companies. In fact, the level of productivity of business depends on effective use of new technologies which is only possible with human resources continuously qualified. For this reason, results will allow us to elaborate recommendations for designing and implementing policies for CVET activities. The present research will be using a methodological approach framed by the ISSTAL (Interdisciplinary, Sequential-Specificity, Time-Allocation, Life-Span) model of social participation (Smith, 1980), already adapted and tested in USA by Cookson (1986) and in Alentejo and other EU regions by Figueira & others (2008) for studying adult participation in learning activities. The study will use a cross-sectional survey complemented by a focus group strategy to discuss survey results by continuing training specialists and practitioners and by a set of case studies to further understanding nature of the participation factors. The cross-sectional survey will use an instrument specifically developed to collect data from a two-stage stratified random sample drawn from a population constituted by technical working people of the two main sectors in the above Portuguese continental regions. According to results from previous studies, it will be expected that the ISSTAL model will be useful for explaining and understanding participation of adults in continuing training activities concerning the sectors of activity under analysis. The study will give an important contribution for promoting equal access to CVET for all workers, as a relevant pathway for a sustainable development of the Portuguese society.